PENGARUH PERIKLANAN MELALUI MEDIA TELEVISI DAN HARGA TERHADAP MINAT BELI SABUN PEMBERSIH WAJAH MEREK MEN’S BIORE DI KOTA PONTIANAK - B11110105, ERLANDA CHRISANDI (Jurnal Manajemen Update, 2015)
This study aims to determine the effect of advertising on television and the price of the buying interest. This study was designed as an explanatory research. Population of this study were men who have been or have not used the products facial cleanser for men Men's Biore brand. This study uses accidental sampling with a sample size of 100 people. The analysis technique used is multiple linear regression analysis using SPSS version 17.0. Based on the due diligence performed models showed the model in this study deserves to dilakukn testing. Results of the analysis showed that the variables of television advertising does not have a significant influence on the variable interest in buying cleaning products Men's Biore face of the brand. As for the price variables have a significant influence on the variable interest in buying cleaning products Men's Biore face of the brand. Keywords : television ads. Price, buying interest